THE LAND PLANT δ13C RECORD AND PLANT EVOLUTION IN THE LATE PALAEOZOIC - Peters-Kottig W.; Strauss H.; Kerp H. (My University, 2006)
Based on the evaluation of 1323 carbon isotope values for Silurian to Permian terrestrial organic carbon, measured on plant fossils, cuticules, humic coals and bulk terrestrial organic matter (TOM), we conclude that the temporal trend in δ13CTOM records variations in the global carbon cycle, notably an increase in the fractional burial of light (terrestrial) organic matter in Late Palaeozoic sediments. δ13CTOM values suggest that the Late Palaeozoic pO2 peak could have been restricted to a time frame of ~ 40 Ma. Carbon isotope data from four taxonomic groups reveal small differences that could be a consequence of habitat conditions. No significant differences in organic carbon isotopic composition in relation to variable climatic conditions are discernible. The carbon isotopic composition solely reflects C3 plant metabolism. © 2006 Elsevier B.V. All rights reserved.
Keywords: C-13/C-12; ORGANIC CARBON; PALAEOZOIC; PO2; TERRESTRIAL; Permian; Silurian; Paleozoic::Permian; Палеозой::Пермская; Paleozoic::Silurian; Палеозой::Силурийская